DEVELOPMENTAL SEQUENCES OF NEGATION BY LEARNERS OF EFL:A Case Study On Seventh Grade Students Of One Private Secondary School In Bandung - Triarisanti, Risa (2013)
This study aims to investigate the developmental sequence of negation that the seventh grade students of secondary school go through in acquiring English negation. This study is largely qualitative and longitudinal. The participants include 34 seventh grade students of one private secondary school in Bandung. However, only 24 students constantly produced negation. Their utterances containing negation gathered through the observation, the picture description test and essay writing were used as the main data of the study. All data obtained from all sources is analysed through the theories of developmental sequence of negation by Ellis (1996), Lightbown & Spada (2011), and Meisel (2011). The sequence includes four stages, i.e. stage 1 (external negation), stage 2 (internal negation 1), stage 3 (internal negation 2), and stage 4 (target-like negation). The findings show that the students are able to produce negation. The total occurences of the negation in a period of approximately six months include 1271 utterances, which consist of grammatical and ungrammatical productions of negation. Further, this study confirms that the four stages in previous studies are evidenced in students' negation. However, this study finds some variation in the order of the stages across periods, although in the last period the order evidenced in the previous studies are confirmed. Keywords: developmental sequence, negation, interlanguage